Oral inactivated whole cell vaccine for mucosal immunization: ETVAX case study - Walker, Richard I.; Bourgeois, A. Louis (Frontiers in Immunology, 2023)
Oral immunization is an effective strategy for inducing protective immunity against mucosal enteric pathogens. Although live-attenuated as well as subunit approaches have been explored for vaccination against enteric pathogens, inactivated whole bacterial cells may also be effective in introducing protective immunity. Successfully accomplishing this goal with inactivated whole bacterial cells will require that a complex antigenic repertoire be presented in controlled immunogenic amounts, in a safe and relatively simple and self-contained delivery format. The benefit from immunization with whole cell vaccines can be further enhanced through genetic engineering to over-express selected antigens and also by the use of mucosal adjuvants to direct a more robust immunologic response. These steps are being taken for the development of ETVAX, the most clinically advanced vaccine candidate against the major enteric pathogen, enterotoxigenic Escherichia coli (ETEC) with significant positive impact.